Consumer immobility predicts both macroeconomic contractions and household poverty during COVID-19 - Headey, Derek D.; Cho, Ame; Lambrecht, Isabel B.; Maffioli, Elisa Maria; Toth, Russell (International Food Policy Research Institute, 2021)
Amid extreme uncertainty during the COVID-19 pandemic, economic policymakers have struggled to respond to rapidly changing circumstances with appropriate speed and scale. One obstacle is the dearth of real-time indicators of the pandemic’s economic impacts, especially in low and middle income countries (LMICs). Here we show that an ‘immobility’ indicator from GoogleTM – measuring the extent to which consumers are staying at home more – is a powerful predictor of changes in household poverty in Myanmar, as well as aggregate national consumption and gross domestic product (GDP) in cross-country data. Combined, this evidence suggests that real-time mobility indicators have the potential to inform a wide range of deliberations, including forecasting models, fine-tuning the timing of both economic stimulus and social protection interventions, and tracking economic recovery from this unprecedented crisis.